2002
DOI: 10.1016/s0736-0266(02)00044-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mechanical stability on local vascularization and tissue differentiation in callus healing

Abstract: To investigate the influence of the stability of an osteotomy fixation on the local vascularization and tissue differentiation in callus healing, a transverse osteotomy of the right metatarsal with a gap size of 2 mm was performed in 10 sheep and stabilized with an external fixator. This fixator permitted a defined axial movement. Two groups of 5 sheep were each operated upon to allow 0.2 mm (group A) or 1 mm (group B) of axial movement. Nine weeks after surgery, the callus was dissected and histological secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
1
9

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(162 citation statements)
references
References 12 publications
6
141
1
9
Order By: Relevance
“…The presence of lamellar bone at right angles or perpendicular to the long axis of the bone implies a point of structural weakness not fully strengthened until remodelling the osteons of repair bone along the longitudinal axis (Olerud and Danckwardt-Lilliestrom, 1968;Perren et al, 1969;Schenk and Willenegger, 1967;Shapiro, 1988). Studies of bone defect models in stable environments help to identify the specific effects on repair of the size and stability of the gap (Claes et al, 1997;Perren, 1979) and the effects of mechanical stability on repair bone vascularity (Claes et al, 2002).…”
Section: Direct Bone Repair (Circular Defect)mentioning
confidence: 99%
“…The presence of lamellar bone at right angles or perpendicular to the long axis of the bone implies a point of structural weakness not fully strengthened until remodelling the osteons of repair bone along the longitudinal axis (Olerud and Danckwardt-Lilliestrom, 1968;Perren et al, 1969;Schenk and Willenegger, 1967;Shapiro, 1988). Studies of bone defect models in stable environments help to identify the specific effects on repair of the size and stability of the gap (Claes et al, 1997;Perren, 1979) and the effects of mechanical stability on repair bone vascularity (Claes et al, 2002).…”
Section: Direct Bone Repair (Circular Defect)mentioning
confidence: 99%
“…A stable environment has long been thought to favor the formation of an intact vascular network (Claes et al, 2002;Glowacki, 1998), and this oxygen-rich environment appears to support the differentiation of skeletal progenitor cells into osteoblasts. One possibility is that a vascular network fails to form around the Mmp9 -/-stabilized fracture or the Mmp9 -/-implant site (Fig.…”
Section: Mmp9 Mediates An Angiogenic Switch During Bone Regenerationmentioning
confidence: 99%
“…17 Structural stability is considered as a crucial factor for bone healing. 45,46 Biomechanical studies have already suggested that plate fixation provides significant structural stability in itself, 47 and through this stability, the normal process of fracture healing continues without restrictions. Therefore, it is questionable whether bone grafts are needed for structural stability.…”
Section: Discussionmentioning
confidence: 99%